1997
DOI: 10.1023/a:1025759408417
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of the present study was to develop the Toddler Behavior Screening Inventory (TBSI) for rapidly assessing maternal reports of toddler behavior problems. The TBSI is a 40-item measure intended for use by pediatricians, psychologists, and other child-care professionals. A group of mothers (n = 312) rated the initial 93-item TBSI in terms of behavior frequency and parental perception of the behavior as problematic. Following item elimination, 40 items were retained due to being both frequent and probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This questionnaire has good psychometric properties, with test-retest reliabilities of .68 to .92 and internal consistency coefficients ranging from .66 to .95 (Achenbach & Rescorla, 2001). The concurrent validity is supported by correlations (r = .54-.77; Achenbach & Rescorla, 2001) between the CBCL and other related rating scales such as the Toddler Behavior Screening Inventory (Mouton-Simien, McCain, & Kelley, 1997).…”
Section: Pre-injury Measuresmentioning
confidence: 99%
“…This questionnaire has good psychometric properties, with test-retest reliabilities of .68 to .92 and internal consistency coefficients ranging from .66 to .95 (Achenbach & Rescorla, 2001). The concurrent validity is supported by correlations (r = .54-.77; Achenbach & Rescorla, 2001) between the CBCL and other related rating scales such as the Toddler Behavior Screening Inventory (Mouton-Simien, McCain, & Kelley, 1997).…”
Section: Pre-injury Measuresmentioning
confidence: 99%
“…Existing instruments, such as the Eyberg Child Behavior Inventory [7] or the Toddler Behavior Screening Inventory [8], only measure problem behaviour and do not address social-emotional competencies. Measuring delays in social-emotional competence, however, is also important since delays in competence are for instance related to internalising and externalising problems later in life [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many parents and professionals believe that early behavior problems are transitory and will decrease over time (Briggs-Gowan, Carter, Bosson-Heenan, Guyer, & Horwitz, 2006). However, these behaviors do not remit for all infants, and accurate identification of those at risk for long-term behavior problems is an important step in providing preventive interventions (Mouton-Simien, McCain, & Kelley, 1997). Signs of atypical development for this young age include differences in the frequency, intensity, and duration of behaviors in comparison to a normative sample, and recent research has demonstrated that behavior problems can be reliably measured in infants as young as 12 months (Carter et al, 2004; Carter, Briggs-Gowan, Jones, & Little, 2003; van Zeijl, Mesman, Stolk, et al, 2006).…”
mentioning
confidence: 99%